Perfect phrases for lead generation : - Brooks, William T. (McGraw-Hill, 2008)
Prospecting for new customers is a key part of every salesperson's job-and perhaps the most challenging part. Your leads, your approach, your timing, everything needs to be perfect. That's why you need Perfect Phrases for Lead Generation by renowned sales guru Bill Brooks. He's assembled a winning collection of proven sales strategies for the 21st century-each linked with appropriate phrases for every customer scenario. Using his surefire selection of targeted phrases